Rare earth element doped hydrogen evolution electrocatalyst and preparation method and application thereof
By doping rare earth elements into nickel oxide and anchoring ruthenium atoms, a rare earth element-doped hydrogen evolution electrocatalyst was prepared, which solved the problems of slow reaction kinetics of alkaline hydrogen evolution electrocatalysts and high use of precious metals in the prior art, and achieved efficient and stable hydrogen generation.
Patent Information
- Application Number
- CN202411849743.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing alkaline hydrogen evolution electrocatalysts have slow reaction kinetics during the electrolytic water hydrogen production process, resulting in additional energy consumption and high use of precious metals, limiting their large-scale application.
Rare earth element doped hydrogen evolution electrocatalyst is prepared by doping rare earth elements into nickel oxide (NiO) and anchoring ruthenium (Ru) atoms. This method enhances adsorption of hydroxyl groups through doping of oxygen-philic rare earth elements, promotes hydrogen conversion on the Ru surface, realizes the synergistic effect of the catalyst, and improves the dissociation rate of water.
It realizes efficient catalytic hydrogen generation in an alkaline environment, and only requires an overpotential of 38mV to reach a current density of 10mA cm-2, and the overpotential did not attenuate during the 50-hour stability test, demonstrating good stability and catalytic activity.
Smart Images

Figure CN119663353A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method of a novel hydrogen evolution electrocatalyst, in particular to a rare earth element-doped hydrogen evolution electrocatalyst and a preparation method and application thereof, belonging to the technical field of nanomaterial preparation and application. Background Art
[0002] Reducing fossil fuel consumption and developing new, clean, renewable energy sources are key strategic priorities. Hydrogen, with its numerous advantages, including high energy density, high calorific value, and zero emissions, is poised to become a powerful driver of a future low-carbon economy. Traditional methods of hydrogen production, such as coal-to-hydrogen and methane reforming, are constrained by high carbon emission restrictions. In contrast, hydrogen production from water electrolysis (HER) offers numerous advantages, such as high efficiency and environmental friendliness, providing a technological path for producing high-purity hydrogen.
[0003] Water electrolysis under alkaline conditions is a widely applicable large-scale hydrogen production technology. However, in the actual process of water electrolysis, the slow reaction kinetics caused by insufficient proton supply seriously increases the additional energy consumption. The specific reaction formula is:
[0004] Vomler step: H2O+e - →H*+OH -
[0005] Heyrovsky step: H* + H2O → OH- + H2
[0006] Tafel step: H*+H*→H2
[0007] In the above formula, it can be found that in alkaline environment, protons come from the dissociation of water (Vomler step). In order to accelerate the kinetics of hydrogen production by electrolysis of water in alkaline medium, the rational design and preparation of alkaline hydrogen evolution electrocatalysts become the key. At present, the best performing materials for alkaline hydrogen evolution electrocatalysts are still electrocatalysts containing precious metals, and their high price limits their potential for large-scale application. If non-precious metals and precious metals are used together through heterogeneous engineering, the amount of precious metals used can be greatly reduced, thereby improving the mass activity of precious metals in electrocatalysts.
[0008] Among the many alkaline hydrogen evolution electrocatalysts, ruthenium (Ru)-based catalysts have a high water dissociation ability and appropriate Ru-H bond strength, which has attracted widespread attention from researchers. By heterogeneous engineering, metal-supported catalysts can be prepared to improve the catalyst efficiency. Lin et al. loaded Ru single atoms on WC xThe adsorption of hydroxyl groups on the carbide support and hydrogen intermediates on the single-atom ruthenium site is balanced, thus enhancing the alkaline HER activity. Qin et al. loaded Ru clusters on vacancy-rich amorphous CeO2. This unique heterostructure accelerated the water dissociation rate and hydrogen desorption kinetics, and the metal support synergistically improved the alkaline HER activity.
[0009] Loading Ru on nickel oxide (NiO) electrocatalysts can promote hydrogen conversion on the Ru surface and significantly reduce Ru usage. However, NiO also has disadvantages. Its insufficient adsorption of OH- leads to an insufficient dissociation rate of H2O molecules and an insufficient proton concentration on the Ru surface, which directly reduces the kinetics of the hydrogen evolution reaction. Therefore, NiO modification is still necessary to improve its electrocatalytic performance. Summary of the Invention
[0010] The main purpose of the present invention is to provide a rare earth element doped hydrogen evolution electrocatalyst and a preparation method thereof, so as to overcome the deficiencies of the prior art.
[0011] Another object of the present invention is to provide applications of the rare earth element-doped hydrogen evolution electrocatalyst.
[0012] To achieve the aforementioned object of the invention, the technical solutions adopted by the present invention include:
[0013] An embodiment of the present invention provides a rare earth element-doped hydrogen evolution electrocatalyst, which includes rare earth element-doped nickel oxide as a carrier, and ruthenium atoms anchored on the carrier.
[0014] The present invention also provides a method for preparing a rare earth element-doped hydrogen evolution electrocatalyst, which comprises:
[0015] A nickel source, a rare earth element source, a MOF precursor, and an organic solvent are mixed to form a mixed solution; water and alcohol are then added to obtain a hydrothermal reaction system;
[0016] allowing the hydrothermal reaction system to undergo a first hydrothermal reaction to obtain a rare earth element / Ni-MOF precursor material;
[0017] Mixing the rare earth element / Ni-MOF precursor material with water to perform a second hydrothermal reaction to obtain a rare earth element / NiO material;
[0018] The rare earth element / NiO material is fully contacted with and adsorbed with a ruthenium source, and then freeze-dried to obtain a rare earth element / NiO-Ru precursor material;
[0019] The rare earth element / NiO-Ru precursor material is annealed in a protective atmosphere to obtain a rare earth element / NiO material anchored with ruthenium atoms, namely a rare earth element-doped hydrogen evolution electrocatalyst.
[0020] The embodiment of the present invention also provides a rare earth element doped hydrogen evolution electrocatalyst prepared by the above preparation method.
[0021] The embodiment of the present invention also provides the use of the aforementioned rare earth element-doped hydrogen evolution electrocatalyst in the hydrogen production reaction by electrolysis of water.
[0022] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0023] The rare earth element-doped hydrogen evolution electrocatalyst provided by the present invention enhances the adsorption of hydroxyl groups by doping NiO with oxygen-philic rare earth elements. The rare earth element / NiO support promotes hydrogen conversion on the Ru surface. The rare earth element / NiO and Ru have a clear synergistic effect, jointly promoting the dissociation of water. It shows high catalytic activity in alkaline HER, providing a new idea for accelerating the kinetics of alkaline HER reaction. In alkaline HER tests, the rare earth element-doped hydrogen evolution electrocatalyst of the present invention only needs an overpotential of 38mV to reach 10mA cm -2 The current density was 200 nm; after 50 h of stability test, the overpotential did not decay. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still fall within the scope of the present invention.
[0025] Figure 1 This is a schematic diagram of the preparation process of a rare earth element-doped hydrogen evolution electrocatalyst in Example 1 of the present invention;
[0026] Figure 2a 、 Figure 2b This is a scanning electron microscope image of NiO-Ru@NF prepared in Comparative Example 3 of the present invention;
[0027] Figure 2c 、 Figure 2d This is a scanning electron microscope image of Ce / NiO-Ru@NF prepared in Example 1 of the present invention;
[0028] Figure 3 This is the XPS spectrum of Ce / NiO-Ru@NF prepared in Example 1 of the present invention;
[0029] Figure 4a LSV curves of NiO, Ce / NiO, NiO-Ru, Ce / NiO-Ru, and commercial Pt / C catalysts;
[0030] Figure 4b The Tafel slope curves of NiO, Ce / NiO, NiO-Ru, Ce / NiO-Ru, and commercial Pt / C catalysts are shown;
[0031] Figure 4c A comparison chart of the catalyst performance of NiO-Ru, Ce / NiO-Ru, and commercial Pt / C catalysts;
[0032] Figure 4d This is a chronopotentiometry curve of the Ce / NiO-Ru catalyst prepared in Example 1 of the present invention;
[0033] Figure 5a and Figure 5b This is a scanning electron microscope image of the catalyst prepared in Example 2 of the present invention;
[0034] Figure 6a and Figure 6b This is a scanning electron microscope image of the catalyst prepared in Example 3 of the present invention;
[0035] Figure 7a and Figure 7b This is a scanning electron microscope image of the catalyst prepared in Example 4 of the present invention;
[0036] Figure 8a and Figure 8b This is a scanning electron microscope image of the catalyst prepared in Example 5 of the present invention;
[0037] Figure 9a The LSV curves of the catalysts prepared in Examples 1, 2, and 3 of the present invention are shown;
[0038] Figure 9b The LSV curves of the catalysts prepared in Examples 1, 4 and 5 of the present invention are shown. DETAILED DESCRIPTION
[0039] In the prior art, there have been many studies on improving the performance of electrocatalytic hydrogen evolution by modifying the oxide support, among which doping is a more common method. In order to solve the problem of insufficient adsorption of OH- by NiO, oxygen-philic rare earth elements (such as La, Ce, Pr, Lu, Dy, etc.) are selected to dope it, which can enhance the adsorption of OH-, thereby promoting the dissociation rate of water. On the other hand, after doping the NiO support, the NiO lattice is distorted, resulting in differential changes in the binding between the oxide support surface and Ru, which promotes the conversion of hydrogen on its surface to a certain extent. At present, there are few reports on using this strategy to improve the performance of electrocatalytic hydrogen evolution.
[0040] Furthermore, this catalyst material can be grown very uniformly in situ on the nickel foam skeleton. In-situ growth in nickel foam improves conductivity, ensuring that the catalyst is connected at the smallest possible unit, ensuring good electron conduction efficiency. Furthermore, the porous nature of the nickel foam electrode maximizes the utilization rate of the electrocatalyst per unit area.
[0041] To address the above issues and to improve the electrocatalytic HER efficiency of metal-supported catalysts in alkaline media, the present invention proposes to dope cheap and easy-to-prepare NiO with oxygen-philic rare earth elements, and then anchor Ru atoms on the oxide support to prepare a new high-performance HER electrocatalyst.
[0042] The technical solution, its implementation process and principles are further explained below.
[0043] One aspect of an embodiment of the present invention provides a rare earth element-doped hydrogen evolution electrocatalyst comprising rare earth element-doped nickel oxide as a carrier, and ruthenium atoms anchored on the carrier.
[0044] In some embodiments, the rare earth element may include any one of cerium (Ce), lanthanum (La), praseodymium (Pr), etc., but is not limited thereto.
[0045] In some embodiments, the content of the rare earth element in the rare earth element-doped hydrogen evolution electrocatalyst is 2.5-7.5 wt %.
[0046] In some embodiments, the rare earth element-doped hydrogen evolution electrocatalyst has a linear nanosheet structure, and the linear nanosheets are stacked on each other.
[0047] Furthermore, the linear nanosheets have a length of 5 to 20 μm, a width of 1 to 3 μm, and a thickness of less than 0.5 μm.
[0048] Another aspect of the present invention provides a method for preparing a rare earth element-doped hydrogen evolution electrocatalyst, which proposes doping cheap and easy-to-prepare NiO with an oxygen-philic rare earth element, and then anchoring Ru atoms on the oxide support to prepare a new high-performance HER electrocatalyst rare earth element / NiO-Ru.
[0049] In some embodiments, the method for preparing the rare earth element-doped hydrogen evolution electrocatalyst comprises:
[0050] A nickel source, a rare earth element source, a MOF precursor, and an organic solvent are mixed to form a mixed solution; water and alcohol are then added to obtain a hydrothermal reaction system;
[0051] allowing the hydrothermal reaction system to undergo a first hydrothermal reaction to obtain a rare earth element / Ni-MOF precursor material;
[0052] Mixing the rare earth element / Ni-MOF precursor material with water to perform a second hydrothermal reaction to obtain a rare earth element / NiO material;
[0053] The rare earth element / NiO material is fully contacted with and adsorbed with a ruthenium source, and then freeze-dried to obtain a rare earth element / NiO-Ru precursor material;
[0054] The rare earth element / NiO-Ru precursor material is annealed in a protective atmosphere to obtain a rare earth element / NiO material anchored with ruthenium atoms, namely a rare earth element-doped hydrogen evolution electrocatalyst.
[0055] In some embodiments, the rare earth element in the rare earth element source may include at least any one of cerium (Ce), lanthanum (La), praseodymium (Pr), etc., but is not limited thereto.
[0056] In some embodiments, the rare earth element source can be any one of cerium nitrate (Ce(NO3)3), lanthanum nitrate (La(NO3)3), praseodymium nitrate (Pr(NO3)3), etc., preferably cerium nitrate, but not limited thereto.
[0057] Furthermore, the nickel source may be NiCl2, but is not limited thereto.
[0058] In some embodiments, the molar ratio of the nickel source, the rare earth element source, and the MOF precursor is 1:(0.025-0.075):3.
[0059] Furthermore, the MOF precursor may be terephthalic acid (TPA), but is not limited thereto.
[0060] In some embodiments, the organic solvent may be N,N-dimethylformamide (DMF), but is not limited thereto.
[0061] In some embodiments, the molar volume ratio of the nickel source to the organic solvent is 0.5-2 mmol: 17.5-70 mL.
[0062] Furthermore, the volume ratio of the organic solvent, water and alcohol is 17.5-70:1.25-5:1.25-5.
[0063] Furthermore, the alcohol may be ethanol, but is not limited thereto.
[0064] In some preferred embodiments, the preparation method comprises: stirring the mixed solution at room temperature for 30 minutes to 2 hours, then adding water and alcohol, and continuing stirring to obtain a hydrothermal reaction system.
[0065] In some embodiments, the temperature of the first hydrothermal reaction is 100-140° C., and the time is 12-24 hours.
[0066] In some embodiments, the temperature of the second hydrothermal reaction is 160-200° C., and the time is 5.5-6.5 hours.
[0067] In some embodiments, the ruthenium source may be RuCl 3 , but is not limited thereto.
[0068] In some preferred embodiments, the preparation method includes: immersing the rare earth element / NiO material in a ruthenium source aqueous solution and performing adsorption.
[0069] Furthermore, the immersion time is 0.5h to 4h.
[0070] Furthermore, the concentration of the ruthenium source aqueous solution is 1 to 5 mg mL -1 .
[0071] In some embodiments, the freeze-drying temperature is -80 to -40°C, and the time is 18 to 48 hours.
[0072] In some embodiments, the annealing treatment is performed at a temperature of 250 to 400° C. and for a time of 1 to 4 hours.
[0073] Furthermore, the protective atmosphere includes, but is not limited to, argon atmosphere.
[0074] In some more specific embodiments of the present invention, the inventors believe that when the water splitting HER half-reaction is carried out in an alkaline medium, a strong interaction occurs between the support composed of rare earth element-doped nickel oxide and the anchored ruthenium. Taking Ce as an example of the rare earth element, the preparation method of the rare earth element-doped hydrogen evolution electrocatalyst (HER catalyst) is specifically that the Ru site adsorbs hydrogen, and the Ce / NiO support adsorbs hydroxyl groups, thereby causing HO...H to split into *H and *OH, thereby accelerating the vomler step. A large amount of H surrounds the Ru site, creating a local proton-rich environment. In this case, the proton availability of the Ru site is greatly improved, thereby accelerating the conversion of H* to H2.
[0075] The preparation method of the HER catalyst comprises the following steps:
[0076] (1) Commercial nickel foam was ultrasonically cleaned in acetone, ethanol and deionized water in sequence, then soaked in 1M hydrochloric acid, and ultrasonically cleaned three times with deionized water. Finally, it was placed in a vacuum oven at 60°C to dry for later use.
[0077] (2) Weigh a certain amount of NiCl2·6H2O, Ce(NO3)3·6H2O and terephthalic acid (TPA) in turn and add them to N,N-dimethylformamide (DMF) to obtain a mixed solution. After stirring at a constant speed for a certain period of time at room temperature, add a certain amount of water and ethanol and continue stirring. After the mixing is sufficiently uniform, transfer the mixed solution to the PTFE lining of the reactor and put a clean piece of foam nickel into it. After the reactor is sealed, carry out a hydrothermal reaction in a hydrothermal box. After the reaction is completed, cool it naturally to room temperature. After taking out the sample, rinse it with deionized water and ethanol alternately and put it in a 60℃ vacuum oven to dry for use.
[0078] (3) placing the nickel foam with the precursor prepared in step (2) into the inner lining of a reactor filled with deionized water, sealing the reactor and performing a hydrothermal reaction; after the reaction is completed, taking out the sample, washing it alternately with deionized water and ethanol, and then placing it in a 60° C. vacuum oven to dry for use.
[0079] (4) The sample in step (3) was placed in a RuCl3·xH2O solution of a certain concentration and soaked for 2 hours for adsorption; after being taken out, it was freeze-dried.
[0080] (5) The sample after freeze-drying in step (4) is annealed in a tube furnace and naturally cooled to room temperature. The annealed sample is rinsed three times with deionized water and then placed in a 60°C vacuum oven for drying, thereby preparing the final HER catalyst.
[0081] In the above step (1), the hydrochloric acid soaking time is controlled to be 10 minutes.
[0082] In the above step (2), the amounts of NiCl2·6H2O, Ce(NO3)3·6H2O and TPA were 1 mmol, 0.05 mmol and 3 mmol, respectively, the amount of DMF was 35 mL, and the amount of water and ethanol was 2.5 mL, respectively.
[0083] In the above step (3), the amount of deionized water added is 40 mL.
[0084] In step (4), the concentration of RuCl3·xH2O solution is 1-5 mg mL -1 , preferably 3 mg mL -1 .
[0085] In the above step (5), the annealing treatment is carried out at 250-400° C. for 1-4 hours in an argon atmosphere.
[0086] Another aspect of the embodiments of the present invention further provides a rare earth element-doped hydrogen evolution electrocatalyst prepared by the aforementioned preparation method.
[0087] In summary, the HER catalyst Ce / NiO-Ru prepared by the present invention, the oxophilic rare earth element Ce doped NiO enhances the adsorption of hydroxyl groups, the Ce / NiO carrier promotes the hydrogen conversion on the Ru surface, Ce / NiO and Ru have a clear synergistic effect, jointly promoting the dissociation of water, and exhibiting high catalytic activity in alkaline HER, providing a new idea for accelerating the reaction kinetics of alkaline HER.
[0088] In some embodiments, in alkaline HER tests, the rare earth element doped hydrogen evolution electrocatalyst (Ce / NiO-Ru) only requires an overpotential of 38 mV to achieve a 10 mA cm -2 The current density was 1.5 GHz and the Tafel slope was 58 mV / dec, indicating fast reaction kinetics. In stability testing, the Ce / NiO-Ru catalyst showed no degradation in performance after 50 hours of continuous operation, demonstrating excellent stability.
[0089] Another aspect of the embodiments of the present invention further provides the use of the aforementioned rare earth element-doped hydrogen evolution electrocatalyst in a hydrogen production reaction by electrolysis of water.
[0090] To further understand the present invention, the technical solution of the present invention will be described in detail below with reference to the embodiments and accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below. In addition, the technical features involved in the various embodiments of the present invention described below may be combined with each other as long as they do not conflict with each other.
[0091] Unless otherwise specified, the raw materials and reagents in the examples of the present invention were purchased from commercial sources.
[0092] Example 1
[0093] The synthesis process of Ce / NiO-Ru@NF catalyst in this embodiment is as follows Figure 1 As shown, first, Ni 2+ 、Ce 3+Ce-doped Ni-MOF (Ce / Ni-MOF@NF) is hydrothermally reacted with TPA in DMF solvent; Ce / Ni-MOF@NF is then pyrolyzed in water solvent to obtain Ce / NiO@NF; finally, Ce / NiO@NF is immersed in RuCl3 solution and annealed in a tube furnace to obtain Ce / NiO-Ru@NF. The process specifically includes the following steps:
[0094] (1) NF cleaning
[0095] The commercial NF was ultrasonically cleaned in acetone, ethanol and deionized water in sequence, then soaked in 1 M hydrochloric acid for 10 min, and then ultrasonically cleaned three times with deionized water. Finally, it was placed in a vacuum oven at 60°C to dry for later use.
[0096] (2) Preparation of Ce / Ni-MOF@NF
[0097] 1mmol NiCl2·6H2O, 0.05mmol Ce(NO3)3·6H2O and 3mmol TPA were weighed in turn and added to 35mL DMF to obtain a mixed solution. After stirring at a constant speed for 30min at room temperature, 2.5mL water and 2.5mL ethanol were added and continued to stir. After mixing sufficiently evenly, the mixed solution was transferred to the PTFE-lined reactor and a clean piece of NF was placed in it. After the reactor was sealed, a hydrothermal reaction was carried out at 125℃ in a hydrothermal box for 24h. After the reaction was completed, it was naturally cooled to room temperature. After taking out the sample, it was rinsed alternately with deionized water and ethanol and placed in a 60℃ vacuum oven to dry for use.
[0098] (3) Preparation of Ce / NiO@NF
[0099] The Ce / Ni-MOF@NF prepared in step (2) was placed in the inner lining of a reactor filled with 40 mL of deionized water. After the reactor was sealed, a hydrothermal reaction was carried out at 180°C for 6 h. After the reaction was completed, the sample was taken out, rinsed alternately with deionized water and ethanol, and then placed in a vacuum oven at 60°C for drying.
[0100] (4) Preparation of Ce / NiO-Ru@NF precursor
[0101] The sample in step (3) was placed in a 3 mg mL -1 The samples were immersed in RuCl3·xH2O solution for 2 h for adsorption; after being taken out, they were freeze-dried at -40℃ for 24 h.
[0102] (5) Preparation of Ce / NiO-Ru@NF
[0103] The sample after freeze-drying in step (4) was annealed at 350°C in an argon atmosphere in a tube furnace for 2 hours and naturally cooled to room temperature. The annealed sample was rinsed three times with deionized water and placed in a 60°C vacuum oven for drying, thereby preparing the final HER catalyst Ce / NiO-Ru.
[0104] Example 2
[0105] (1) NF cleaning
[0106] The commercial NF was ultrasonically cleaned in acetone, ethanol and deionized water in sequence, then soaked in 1 M hydrochloric acid for 10 min, and then ultrasonically cleaned three times with deionized water. Finally, it was placed in a vacuum oven at 60°C to dry for later use.
[0107] (2) Preparation of Ce / Ni-MOF@NF
[0108] 1mmol NiCl2·6H2O, 0.025mmol Ce(NO3)3·6H2O and 3mmol TPA were weighed in turn and added to 35mL DMF to obtain a mixed solution. After stirring at a constant speed for 30min at room temperature, 2.5mL water and 2.5mL ethanol were added and continued to stir. After mixing sufficiently evenly, the mixed solution was transferred to the PTFE-lined reactor and a clean piece of NF was placed in it. After the reactor was sealed, a hydrothermal reaction was carried out at 125℃ in a hydrothermal box for 24h. After the reaction was completed, it was naturally cooled to room temperature. After taking out the sample, it was rinsed alternately with deionized water and ethanol and placed in a 60℃ vacuum oven to dry for use.
[0109] (3) Preparation of Ce / NiO@NF
[0110] The Ce / Ni-MOF@NF prepared in step (2) was placed in the inner lining of a reactor filled with 40 mL of deionized water. After the reactor was sealed, a hydrothermal reaction was carried out at 180°C for 6 h. After the reaction was completed, the sample was taken out, rinsed alternately with deionized water and ethanol, and then placed in a vacuum oven at 60°C for drying.
[0111] (4) Preparation of Ce / NiO-Ru@NF precursor
[0112] The sample in step (3) was placed in a 3 mg mL -1 The samples were immersed in RuCl3·xH2O solution for 2 h for adsorption; after being taken out, they were freeze-dried at -40℃ for 24 h.
[0113] (5) Preparation of Ce / NiO-Ru@NF
[0114] The sample after freeze-drying in step (4) was annealed at 350°C in an argon atmosphere in a tube furnace for 2 hours and naturally cooled to room temperature. The annealed sample was rinsed three times with deionized water and placed in a 60°C vacuum oven for drying, thereby preparing the final HER catalyst Ce / NiO-Ru.
[0115] Example 3
[0116] (1) NF cleaning
[0117] The commercial NF was ultrasonically cleaned in acetone, ethanol and deionized water in sequence, then soaked in 1 M acid for 10 min, and then ultrasonically cleaned three times with deionized water. Finally, it was placed in a vacuum oven at 60°C to dry for use.
[0118] (2) Preparation of Ce / Ni-MOF@NF
[0119] 1mmol NiCl2·6H2O, 0.075mmol Ce(NO3)3·6H2O and 3mmol TPA were weighed in turn and added to 35mL DMF to obtain a mixed solution. After stirring at a constant speed for 30min at room temperature, 2.5mL water and 2.5mL ethanol were added and continued to stir. After mixing sufficiently evenly, the mixed solution was transferred to the PTFE-lined reactor and a clean piece of NF was placed in it. After the reactor was sealed, a hydrothermal reaction was carried out at 125℃ in a hydrothermal box for 24h. After the reaction was completed, it was naturally cooled to room temperature. After taking out the sample, it was rinsed alternately with deionized water and ethanol and placed in a 60℃ vacuum oven to dry for use.
[0120] (3) Preparation of Ce / NiO@NF
[0121] The Ce / Ni-MOF@NF prepared in step (2) was placed in the inner lining of a reactor filled with 40 mL of deionized water. After the reactor was sealed, a hydrothermal reaction was carried out at 180°C for 6 h. After the reaction was completed, the sample was taken out, rinsed alternately with deionized water and ethanol, and then placed in a vacuum oven at 60°C for drying.
[0122] (4) Preparation of Ce / NiO-Ru@NF precursor
[0123] The sample in step (3) was placed in a 3 mg mL -1 The samples were immersed in RuCl3·xH2O solution for 2 h for adsorption; after being taken out, they were freeze-dried at -40℃ for 24 h.
[0124] (5) Preparation of Ce / NiO-Ru@NF
[0125] The sample after freeze-drying in step (4) was annealed at 350°C in an argon atmosphere in a tube furnace for 2 hours and naturally cooled to room temperature. The annealed sample was rinsed three times with deionized water and placed in a 60°C vacuum oven for drying, thereby preparing the final HER catalyst Ce / NiO-Ru.
[0126] Example 4
[0127] (1) NF cleaning
[0128] The commercial NF was ultrasonically cleaned in acetone, ethanol and deionized water in sequence, then soaked in 1 M hydrochloric acid for 10 min, and then ultrasonically cleaned three times with deionized water. Finally, it was placed in a vacuum oven at 60°C to dry for later use.
[0129] (2) Preparation of La / Ni-MOF@NF
[0130] 1mmol NiCl2·6H2O, 0.05mmol La(NO3)3·6H2O and 3mmol TPA were weighed in turn and added to 70mL DMF to obtain a mixed solution. After stirring at a constant speed for 2h at room temperature, 2.5mL water and 2.5mL ethanol were added and continued to stir. After mixing sufficiently evenly, the mixed solution was transferred to the PTFE-lined reactor and a clean piece of NF was placed in it. After the reactor was sealed, a hydrothermal reaction was carried out at 100℃ in a hydrothermal box for 24h. After the reaction was completed, it was naturally cooled to room temperature. After taking out the sample, it was rinsed alternately with deionized water and ethanol and placed in a 60℃ vacuum oven to dry for use.
[0131] (3) Preparation of La / NiO@NF
[0132] The La / Ni-MOF@NF prepared in step (2) was placed in the inner lining of a reactor filled with 40 mL of deionized water. After the reactor was sealed, a hydrothermal reaction was carried out at 200°C for 5.5 h. After the reaction was completed, the sample was taken out, rinsed alternately with deionized water and ethanol, and then placed in a vacuum oven at 60°C for drying.
[0133] (4) Preparation of La / NiO-Ru@NF precursor
[0134] The sample in step (3) was placed in a 5 mg mL -1 The samples were immersed in RuCl3·xH2O solution for 0.5 h for adsorption; after being taken out, they were freeze-dried at -40℃ for 18 h.
[0135] (5) Preparation of La / NiO-Ru@NF
[0136] The sample after freeze-drying in step (4) was annealed at 250°C in an argon atmosphere in a tube furnace for 4 hours and naturally cooled to room temperature. The annealed sample was rinsed three times with deionized water and placed in a 60°C vacuum oven for drying, thereby preparing the final HER catalyst La / NiO-Ru.
[0137] Example 5
[0138] (1) NF cleaning
[0139] The commercial NF was ultrasonically cleaned in acetone, ethanol and deionized water in sequence, then soaked in 1 M hydrochloric acid for 10 min, and then ultrasonically cleaned three times with deionized water. Finally, it was placed in a vacuum oven at 60°C to dry for later use.
[0140] (2) Preparation of Pr / Ni-MOF@NF
[0141] 1mmol NiCl2·6H2O, 0.05mmol Pr(NO3)3·6H2O and 3mmol TPA were weighed in turn and added to 17.5mL DMF to obtain a mixed solution. After stirring at a constant speed for 60min at room temperature, 2.5mL water and 2.5mL ethanol were added and continued to stir. After mixing sufficiently evenly, the mixed solution was transferred to the PTFE-lined reactor and a clean NF was placed in it. After the reactor was sealed, a hydrothermal reaction was carried out at 140℃ in a hydrothermal box for 12h. After the reaction was completed, it was naturally cooled to room temperature. After taking out the sample, it was rinsed alternately with deionized water and ethanol and placed in a 60℃ vacuum oven to dry for use.
[0142] (Preparation of 3Pr / NiO@NF
[0143] The La / Ni-MOF@NF prepared in step (2) was placed in the inner lining of a reactor filled with 40 mL of deionized water. After the reactor was sealed, a hydrothermal reaction was carried out at 160°C for 6.5 h. After the reaction was completed, the sample was taken out, rinsed alternately with deionized water and ethanol, and then placed in a vacuum oven at 60°C for drying.
[0144] (4) Preparation of Pr / NiO-Ru@NF precursor
[0145] The sample in step (3) was placed in a 1 mg mL -1 The samples were immersed in RuCl3·xH2O solution for 4 h for adsorption; after being taken out, they were freeze-dried at -80℃ for 36 h.
[0146] (5) Preparation of Pr / NiO-Ru@NF
[0147] The sample after freeze-drying in step (4) was annealed at 400°C in an argon atmosphere in a tube furnace for 1 hour and naturally cooled to room temperature. The annealed sample was rinsed three times with deionized water and placed in a 60°C vacuum oven for drying, thereby preparing the final HER catalyst Pr / NiO-Ru.
[0148] Comparative Example 1 Preparation of NiO@NF
[0149] The difference between this comparative example and Example 1 is that the sample is collected in step (3), and Ce(NO3)3·6H2O is not added in step (2).
[0150] Comparative Example 2 Preparation of Ce / NiO@NF
[0151] The difference between this comparative example and Example 1 is that the sample is collected until step (3), and steps (4) and (5) are not performed.
[0152] Comparative Example 3 Preparation of NiO-Ru@NF
[0153] The difference between this comparative example and Example 1 is that Ce(NO3)3·6H2O is not added in step (2).
[0154] The present invention characterized the products obtained in the above examples and comparative examples, and the results were analyzed as follows:
[0155] Figure 1 The flow chart of catalyst preparation is described. First, Ni 2+ 、Ce 3+ Ce-doped Ni-MOF (Ce / Ni-MOF@NF) was grown on the NF surface by hydrothermal reaction with TPA in DMF solvent. Ce / Ni-MOF@NF was then thermally decomposed in water solvent to decompose the ligand to obtain Ce / NiO@NF, which ensured the connection of the metal-oxygen bond in the catalyst material. Finally, Ce / NiO@NF was immersed in RuCl3 solution. 3+ The adsorption equilibrium was achieved on the Ce / NiO surface, and then annealed in a tube furnace to obtain Ce / NiO-Ru@NF.
[0156] In order to analyze the microscopic morphology of the catalyst material, the inventors of this case conducted a scanning electron microscope test on the catalyst. NiO-Ru@NF and Ce / NiO-Ru@NF were used as the main comparisons of this invention, and the beneficial effects of oxyphilic Ce doping on the catalyst were specifically analyzed. Ensuring uniform loading on the NF skeleton surface is the prerequisite for performance comparison. Figure 2a 、 2bAs shown in the figure, due to the process advantages of the present invention, both NiO-Ru@NF and Ce / NiO-Ru@NF ensure that the catalyst is completely coated on the NF surface without any exposed parts, which ensures the stability of the current generated per unit area in subsequent electrochemical tests. On the other hand, Ce doping has an impact on the micromorphology of the catalyst. NiO-Ru@NF presents a porous sheet morphology ( Figure 2b ), this is because the initial Ni-MOF nucleates and grows uniformly along the NF surface, making the Ni-MOF cross-linked and porous, maintaining uniform characteristics from the perspective of microscopic morphology. At the same time, there is a spacing of about 3μm between the layers, which also reflects the microscopic density of the catalyst. For the Ce-doped catalyst, the micromorphology has changed, resulting in significant differences, such as Figure 2c and Figure 2d Ce / NiO-Ru@NF presents the morphology of linear nanosheets, which are stacked on each other. Analysis shows that the Ce salt is nitrate and the Ni salt is chloride during the initial MOF synthesis. The difference in ionization between the two causes Ce 3+ It preferentially combines with TPA to provide a template for Ni-MOF growth, making the growth of Ce-doped Ni-MOF directional and growing into linear nanosheets. Figure 2d As can be seen from the figure, the width of the nanosheets is about 1 μm, the length is about 10 μm, and the surface is very smooth. In the electrocatalytic reaction, the active sites on the surface of the stacked linear nanosheets have a larger contact area with H2O, OH* and H* in the electrolyte, which is more conducive to the electrocatalytic reaction and provides a prerequisite for accelerating the reaction kinetics. At the same time, the presence of elements in the synthesized catalyst (such as Figure 3 shown).
[0157] The electrochemical tests in this invention were conducted using a three-electrode system in 1 M KOH, with the catalyst serving as the working electrode, a carbon rod as the counter electrode, and Hg / HgO as the reference electrode. It should be noted that Pt has strong HER activity. To standardize the electrochemical tests, Pt sheet / wire / mesh dissolution and subsequent cathode deposition were excluded. A Pt sheet electrode holder and Pt counter electrode were not used. Since the tests were conducted in an alkaline environment, an Hg / HgO reference electrode was used. All potentials were converted from Hg / HgO to RHE. Figure 4a The linear voltammetric sweep curves of the catalysts are compared here. The HER performance of NiO, Ce / NiO, NiO-Ru, Ce / NiO-Ru and commercial Pt / C catalysts is compared here. For NiO and Ce / NiO, it is obvious that they do not have HER activity, and the expected HER activity is 10mA cm -2The current density requires an overpotential of more than 350 mV, which is attributed to the lack of active sites for H conversion in the catalyst. However, it can be observed that the performance of NiO after Ce doping is improved. This phenomenon can be explained that Ce doped NiO enhances *OH adsorption, and the proton concentration required for H conversion at high overpotential is higher, which provides a mechanistic explanation for the subsequent existence of active Ru sites for H conversion. After Ru loading, both NiO-Ru and Ce / NiO-Ru have good catalytic activity, and Ce / NiO-Ru has better performance. This is due to the improved *OH adsorption of Ce-doped NiO analyzed above, and the Ru sites regulated by Ce doping enhance the ability of *H to convert H2 and accelerate the dissociation rate of water. The two have a strong synergistic effect and enhance the alkaline HER performance. At the same time, it can be seen that the catalyst performance of this strategy is higher than that of commercial Pt / C catalysts, reflecting the application potential of Ru-based catalysts. To verify the performance of the catalyst at the kinetic level, Tafel slope analysis is required, such as Figure 4b As shown in the figure, the Tafel slope is consistent with the LSV curve from large to small, NiO (184.5mV dec-1) > Ce / NiO (183.8mV dec-1) > NiO-Ru (85.2mV dec-1) > Pt / C (75.7mV dec-1) > Ce / NiO-Ru (58.2mV dec-1), proving that Ce / NiO-Ru has the fastest reaction kinetics. As the current density increases, the required overpotential is smaller than that of other catalysts. The comparison of overpotential and Tafel slope between the three catalysts with better performance is shown in Figure 4c For HER catalysis, stability is also one of the most critical indicators to measure the quality of the catalyst, such as Figure 4d As shown, Ce / NiO-Ru at 10 mA cm -2 The chronopotentiometry test was carried out under a current density of 1.5 Å, and the catalyst showed strong stability. After 50 h of continuous operation, the overpotential did not increase, and only fluctuations caused by gas escape occurred. This is believed to indicate that Ce / NiO-Ru has excellent HER stability.
[0158] The scanning electron microscope image of the catalyst prepared in Example 2 of the present invention is as follows: Figure 5a and Figure 5b As shown, the LSV curve is Figure 9a The scanning electron microscope image of the catalyst prepared in Example 3 is shown in FIG. Figure 6a and Figure 6b As shown, the LSV curve is Figure 9a shown.
[0159] The scanning electron microscope image of the catalyst prepared in Example 4 of the present invention is as follows: Figure 7a and Figure 7b As shown, the LSV curve is Figure 9bThe scanning electron microscope image of the catalyst prepared in Example 5 is shown in FIG. Figure 8a and Figure 8b As shown, the LSV curve is Figure 9b shown.
[0160] In summary, the catalyst prepared by the present invention and the strategy adopted not only provide a simple and environmentally friendly method for preparing high-performance HER catalysts, but also successfully verify the beneficial effects of the alkaline HER brought about by the catalyst structure design of the present invention. Specifically, it is manifested as follows: (1) The Ce-doped NiO carrier uniformly anchors Ru, showing very excellent HER activity; (2) The oxophilic Ce-doped NiO promotes the adsorption of *OH by the catalyst and its influence on Ru sites promotes the conversion of H on the Ru surface, and on this basis successfully promotes the dissociation of water. The present invention is suitable for the future large-scale production of alkaline HER catalysts and brings considerable economic benefits to hydrogen production at the electrolyzer level.
[0161] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments using other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0162] Obviously, the embodiments of the present invention described above are intended only to illustrate the principles of the present invention and are not intended to limit its implementation. Those skilled in the relevant art may, based on the above description, make other modifications or variations to the present invention. While it is impossible to enumerate all implementations in detail, any clearly derivable variations of the technical solutions are still protected by the present invention.
Claims
1. A rare earth element doped hydrogen evolution electrocatalyst, characterized in that: include: Rare earth element doped nickel oxide as a carrier, and ruthenium atoms anchored on the carrier.
2. The rare earth element doped hydrogen evolution electrocatalyst according to claim 1, characterized in that: The rare earth element comprises at least any one of cerium, lanthanum and praseodymium; and / or the content of the rare earth element in the rare earth element-doped hydrogen evolution electrocatalyst is 2.5-7.5wt%.
3. The rare earth element doped hydrogen evolution electrocatalyst according to claim 1, characterized in that: The rare earth element doped hydrogen evolution electrocatalyst has a linear nanosheet structure, and the linear nanosheets are stacked on each other; preferably, the linear nanosheet has a length of 5 to 20 μm, a width of 1 to 3 μm, and a thickness of less than 0.5 μm.
4. A method for preparing a rare earth element doped hydrogen evolution electrocatalyst, characterized in that: include: Mixing a nickel source, a rare earth element source, a MOF precursor, and an organic solvent to form a mixed solution; Then, water and alcohol are added to obtain a hydrothermal reaction system; Allowing the hydrothermal reaction system to undergo a first hydrothermal reaction to obtain a rare earth element / Ni-MOF precursor material; Mixing the rare earth element / Ni-MOF precursor material with water to perform a second hydrothermal reaction to obtain a rare earth element / NiO material; The rare earth element / NiO material is fully contacted with and adsorbed with a ruthenium source, and then freeze-dried to obtain a rare earth element / NiO-Ru precursor material; The rare earth element / NiO-Ru precursor material is annealed in a protective atmosphere to obtain a rare earth element / NiO material anchored with ruthenium atoms, namely a rare earth element doped hydrogen evolution electrocatalyst.
5. The preparation method according to claim 4, characterized in that: The rare earth element in the rare earth element source includes at least any one of cerium, lanthanum and praseodymium; preferably, the rare earth element source includes at least any one of cerium nitrate, lanthanum nitrate and praseodymium nitrate, preferably cerium nitrate; And / or, the nickel source comprises NiCl2; And / or, the molar ratio of the nickel source, the rare earth element source and the MOF precursor is 1:(0.025-0.075):3; and / or, the MOF precursor comprises terephthalic acid; and / or, the organic solvent comprises N,N-dimethylformamide; and / or, the molar volume ratio of the nickel source to the organic solvent is 0.5-2 mmol:17.5-70 mL; and / or, the alcohol comprises ethanol; and / or, the volume ratio of the organic solvent, water and alcohol is 17.5-70:1.25-5:1.25-5; And / or, the preparation method comprises: stirring the mixed solution at room temperature for 30 minutes to 2 hours, then adding water and alcohol, and continuing stirring to obtain a hydrothermal reaction system.
6. The preparation method according to claim 4, characterized in that: The temperature of the first hydrothermal reaction is 100-140°C and the time is 12-24h; And / or, the temperature of the second hydrothermal reaction is 160-200° C., and the time is 5.5-6.5 hours.
7. The preparation method according to claim 4, characterized in that: The ruthenium source includes RuCl3; And / or, the preparation method comprises: immersing the rare earth element / NiO material in a ruthenium source aqueous solution and adsorbing it, preferably, the immersion time is 0.5h to 4h, preferably, the concentration of the ruthenium source aqueous solution is 1 to 5mg mL- 1 ; And / or, the freeze-drying temperature is -80 to -40°C and the time is 18 to 36 hours.
8. The preparation method according to claim 4, characterized in that: The annealing treatment is performed at a temperature of 250-400° C. for a time of 1-4 hours; and / or the protective atmosphere comprises an argon atmosphere.
9. A rare earth element doped hydrogen evolution electrocatalyst prepared by the preparation method according to any one of claims 4 to 8.
10. Use of the rare earth element doped hydrogen evolution electrocatalyst according to any one of claims 1 to 3 and 9 in a hydrogen production reaction by electrolysis of water.
Citation Information
Patent Citations
Selenium-doped ferronickel spinel / nickel oxyhydroxide composite electrocatalyst material as well as preparation method and application thereof
CN111111707A
Rare earth monatomic-noble metal cluster composite catalyst as well as preparation method and application thereof
CN116445967A
Cited By
Nickel-molybdenum-based rare earth element doped core-shell catalyst for hydrogen production by alkaline electrolysis of water as well as preparation method and application thereof
CN121023576A
Nickel-molybdenum-based rare earth element doped core-shell catalyst for hydrogen production by alkaline electrolysis of water, and preparation method and application thereof
CN121023576B